2007
DOI: 10.1101/gad.1521607
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 modification of the eIF4E cognate 4EHP enhances cap structure-binding activity of 4EHP

Abstract: The expression of the ubiquitin-like molecule ISG15 and protein modification by ISG15 (ISGylation) are strongly activated by interferon, genotoxic stress, and pathogen infection, suggesting that ISG15 plays an important role in innate immune responses. 4EHP is an mRNA 5 cap structure-binding protein and acts as a translation suppressor by competing with eIF4E for binding to the cap structure. Here, we report that 4EHP is modified by ISG15 and ISGylated 4EHP has a much higher cap structure-binding activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
144
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 37 publications
1
144
1
1
Order By: Relevance
“…Plasmid Construction-Construction of pcDNA3.1-hUBE1L, pcDNA3.1-mUbcH8, and pCAGGS-His 6 -mISG15 was described previously (10). FLAG-Herc5 was described previously (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid Construction-Construction of pcDNA3.1-hUBE1L, pcDNA3.1-mUbcH8, and pCAGGS-His 6 -mISG15 was described previously (10). FLAG-Herc5 was described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…Human SUMO1 (NM_003352.4) cDNA was amplified by RT-PCR using the mRNA of HeLa cells. FLAG-SUMO1-PKR, FLAG-ISG15-PKR, and FLAG-PKR-ISG15 fusion proteins were constructed as described previously (10). Site-directed point mutations were generated by the QuikChange XL Site-directed Mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…So far, the biological function of ISGylation has only been elucidated for some cellular target proteins. These include the functional inhibition of enzymes Takeuchi et al, 2006;Zou et al, 2007;Malakhova and Zhang, 2008) and the enhancement of the cap structure-binding activity of the translational suppressor, 4EHP (Okumura et al, 2007). Recent studies have shown that ISGylation negatively regulates the ubiquitin-proteasome pathway by direct interference with polyubiquitination (Desai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitin-like modifier, ISG15 can form covalent conjugates to many cellular proteins, a process termed "protein ISGylation" (12,13). A series of distinct enzymes are involved in the process of protein ISGylation, including ubiquitin-activating enzyme E1 homolog (UBE1L) (14,15), a conjugating enzyme, ubiquitin carrier protein L6 (UBCH8) (E2) (16,17), protein ligases (E3) (18)(19)(20)(21), and an ISG15-specific protease USP18 (22,23), as well as some viral proteins (24). Interestingly, ISG15 and the majority of its modification enzymes are encoded by ISGs (25), indicating that protein ISGylation is a tightly regulated process and plays important roles in immune responses (26).…”
mentioning
confidence: 99%